A note on strandings and entanglements of humpback whales (Megaptera novaeangliae) in Ecuador - Alava , Juan Jose; Barragan , Maria Jose; Castro , Cristina; Carvajal , Raul (J. Cetacean Res. Manage., 2023)
Between June and September of each year, southeastern Pacific humpback whales, Megaptera novaeangliae, arrive on the Ecuadorian coast to reproduce. Between July 2001 and September 2002, seven new strandings of humpback whales were found at different places along the Ecuadorian coast. Three of them were related to incidental catches caused by fishing nets (gillnets) and one of them occurred outside of the humpback whales’ reproductive season. Using non-proportional and proportional 95% confidence interval calculations, it is estimated that the average frequency of strandings of humpback whales is 1.55 individuals per year (95% CI: 0.27,2.83; range: 1-4) since 1994, principally in the central and southern parts of the Ecuadorian coast, and the proportion of strandings due to bycatch is estimated at 0.286 (95% CI: 0.105,0.533). A preliminary mortality rate of 0.035(95% CI: 0.019,0.055), including both unknown and anthropogenic causes is estimated for this stock. 50% of the strandings took place in August and most were registered in 2001 (n=4). Six humpback whales with fishing nets embedded in their pectoral fins and tails were also observed in the marine area of the Machalilla National Park and the island of La Plata July-September. 67% of these entanglements occurred in July, and in one case a mother, accompanied by her calf, was observed with cables and a net on her head. These incidental catches are possibly related to the strandings occurring at the same time along the Ecuadorian shoreline. The fishery device most frequently linked to bycatch is the surface gillnet. Technological changes in fishing gear are vital for the conservation of marine mammals. It is imperative that the Ecuadorian coast be divided into zones and certain areas be delimited for the conservation of humpback whales through agreements with local users of the marine areas.